1979
DOI: 10.7326/0003-4819-91-5-702
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Nonparoxysmal Sinus Tachycardia in Otherwise Healthy Persons

Abstract: Seven patients had chronic, unexplained, nonparoxysmal sinus tachycardia. The clinical, electrocardiographic, and electrophysiologic characteristics of these cases are described. In each case electrocardiographic and electrophysiologic observations suggested that tachycardia was nonparoxysmal and due to increased automaticity of the sinus node (or of an automatic atrial focus located very near the sinus node). The mechanisms of increased sinus node automaticity in these patients were explored using drugs affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
1
5

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(59 citation statements)
references
References 35 publications
1
52
1
5
Order By: Relevance
“…According to the earlier reports, almost all highly symptomatic patients with IST have been women, many of them were hypertensive, and many have been health care workers [6,24,26,27]. The results of our study confirmed that elevated HR was more common among hypertensive than normotensive subjects.…”
Section: Characteristics Of Subjects With Istsupporting
confidence: 94%
“…According to the earlier reports, almost all highly symptomatic patients with IST have been women, many of them were hypertensive, and many have been health care workers [6,24,26,27]. The results of our study confirmed that elevated HR was more common among hypertensive than normotensive subjects.…”
Section: Characteristics Of Subjects With Istsupporting
confidence: 94%
“…A taquicardia sinusal inapropriada é uma arritmia rara, que ocorre em indivíduos, aparentemente, normais, caracterizada por um ritmo taquicárdico crônico (>3 meses de duração), freqüência >100bpm durante vigília, resposta adrenérgica exacerbada e aspecto eletrocardiográfico da onda P, sugestivo de sua origem sinusal 1 . A condição leva, freqüentemente, a sintomas tipo palpitações e cansaço 2 , sendo de difícil controle clínico, mostrando geralmente resposta inadequada ao uso de drogas antiarrítmicas, que reduzem a freqüência sinusal.…”
Section: Modificação Do Nódulo Sinusal Via Cateter Por Energia De Radunclassified
“…Inappropriate sinus tachycardia (IST), first described in 1979 [1], is a fast heart rhythm arising from the sinus node, the normal primary pacemaker of the heart but at an inappropriate high rate. In a 24-hour Holter monitoring patients have an average daily heart rates exceeding 100 bpm but the P-wave morphology during tachycardia is nearly identical to that in sinus rhythm and usually have symptoms of pulsations in the neck, shortness of breath, light-headedness, fatigue, sweating, chest pain, nonparoxysmal palpitations at rest and/or early during exercise associated with a relative or absolute increase in sinus rate out of proportion to physiological need.…”
Section: Introductionmentioning
confidence: 99%